2015
DOI: 10.1007/s11664-015-4024-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bondability of the Epoxy-Enhanced Sn-58Bi Solder with ENIG and ENEPIG Surface Finishes

Abstract: The effect of different surface finishes, electroless nickel immersion gold (ENIG) and electroless nickel electroless palladium immersion gold (EN-EPIG), on the mechanical properties of Sn-58Bi bumps made with solder paste enhanced with epoxy were investigated. The microstructure and fracture surfaces were observed with scanning electron microscopy, and the compositions of the IMC and solder were measured using energy dispersive spectrometry and an electron probe micro-analyzer (EPMA). To evaluate the mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%. In addition, the suppress effect of the IMC was observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder.…”
Section: 22mentioning
confidence: 76%
See 1 more Smart Citation
“…Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%. In addition, the suppress effect of the IMC was observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder.…”
Section: 22mentioning
confidence: 76%
“…Meanwhile, Yang et al [106] pointed out the UTS of Sn-Bi + 0:07 wt% composite solder had no obvious change compared with the plain solder, and the elongation and creep properties show a great improvement. Moreover, the improvement phenomenon of mechanical properties is observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder. [50] demonstrated that the doping of TiO 2 could have resulted in the refinement of microstructure of Sn-0.7wt%Cu-0.05 wt%Ni solder by the fabricate process of microwave sintered and the homogeneous (Cu, Ni) 6 Sn 5 intermetallics appear in the grains of particles.…”
Section: Mechanical Propertiesmentioning
confidence: 82%
“…Therefore, researchers are moving toward low melting point solders like Sn–Zn (the eutectic point at 199 °C), Sn–Bi (the eutectic point at 139 °C), or Sn–In (the eutectic point at 118 °C) alloys which are becoming more and more important to address these issues. , Among these, Sn-58 Bi eutectic alloy has received a lot of interest due to its comparatively low melting point over conventional Sn–Pb (eutectic point at 183 °C) alloy. , Because Sn–Bi solder has a relatively higher melting temperature than Sn–In, it is less expensive and has better thermal reliability . Also, compared to Sn–Zn, it is less prone to oxidation at elevated temperatures. ,, The mechanical characteristics of Sn–Bi alloy in polymer matrices have also been investigated. , Notably, Sn–Bi alloys could be reasonably used to bond electronic components onto smart flexible or wearable fabrics at 180 °C for 60 s , Sn–Bi eutectic solder does, however, have some shortcomings, including poor fatigue and low ductility due to the brittle Bi-rich phase. Brittle Bi phase coupled with intermetallic compounds (IMCs) at the solder/substrate interface raises reliability questions because the bending of flexible printed circuit boards (FPCBs) could result in mechanical shock …”
Section: Introductionmentioning
confidence: 99%
“…The cured epoxy resin after the reflow process can adhere to the joint surface and form a composite structure to provide extra mechanical support. Seung-Boo Jung et al [ 12 , 13 , 14 ] conducted much research on the mechanical properties and reliability of epoxy-containing Sn-Bi solder paste. It was found that after reflow soldering, the cured epoxy provided an extra bonding effect with the substrate, which increased the shear strength and anti-drop performance of the Sn-Bi epoxy solder joint [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seung-Boo Jung et al [ 12 , 13 , 14 ] conducted much research on the mechanical properties and reliability of epoxy-containing Sn-Bi solder paste. It was found that after reflow soldering, the cured epoxy provided an extra bonding effect with the substrate, which increased the shear strength and anti-drop performance of the Sn-Bi epoxy solder joint [ 12 , 13 ]. It was found that during aging, Sn-58Bi epoxy solder joints had a lower IMC (intermetallic compound) growth rate and better mechanical properties than Sn-58Bi solder joints due to the blocking effect of epoxy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%